Researching the natural history trade of the nineteenth century. Issue 1 (2nd January 2020) - Ville, Simon
ABSTRACT: The archives of the Australian Museum and the Macleay Museum are deployed to analyse the global trading networks of two important Australian natural history collectors in the mid-nineteenth century. The evidence reveals much about the challenges they faced transacting in heterogeneous specimens over long distances. It also uncovers some of the solutions they pursued, particularly in choosing the appropriate type of transaction, forging trust-based trading networks, obtaining up-to-date scientific information, and drawing on the infrastructure of existing, regular commodity trades.